Development And Characterisation Of Electrospun Solid Dispersions Of Atovaquone For Enhanced Buccal Drug Delivery - Teoh, Xin Yi (2023)
The present study investigated a poorly aqueous soluble drug, atovaquone (ATQ) formulated using an electrospinning solid dispersion strategy with polymer carrier systems. Thermal treatment was applied to ATQ form I and reported heat-sensitive properties where it sublimates and degrades before melting temperature. Following the thermal treatment, a new polymorph (ATQ form sub/eva) was obtained as a result of sublimation and evaporation. Besides, an anomalous stepwise transition circa -20°C was identified from the ATQ produced via melt-quenching demonstrating the possibility of ATQ amorphisation. Subsequently, a non-heat invasive electrospinning technique was utilised to produce solid dispersions of ATQ with the polymer PVPVA or/and PVP. High content recovery of ATQ electrospun samples was quantitated by a novel HPLC method developed herein. Hydrogen bonding interactions between ATQ and polymers were identified through ATR-FTIR analysis. A reduction of ATQ crystallinity was confirmed in the electrospun samples and the ATQ electrospun solid dispersions have been shown to improve the solubility and drug release profiles compared to the raw crystalline ATQ. However, there was no proportional relationship between the degree of crystallinity reduction and the improvement of the drug release profile reported. Instead, an optimisation of the hydrophilic-hydrophobic balance of the polymeric system was highlighted to sustain the supersaturation state by preventing solution-mediated recrystallisation of the electrospun samples.